2015
DOI: 10.1371/journal.pone.0141312
|View full text |Cite
|
Sign up to set email alerts
|

An Anti-Influenza Virus Antibody Inhibits Viral Infection by Reducing Nucleus Entry of Influenza Nucleoprotein

Abstract: To date, four main mechanisms mediating inhibition of influenza infection by anti-hemagglutinin antibodies have been reported. Anti-globular-head-domain antibodies block either influenza virus receptor binding to the host cell or progeny virion release from the host cell. Anti-stem region antibodies hinder the membrane fusion process or induce antibody-dependent cytotoxicity to infected cells. In this study we identified a human monoclonal IgG1 antibody (CT302), which does not inhibit both the receptor binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…A/Brisbane/10/2007-ma (H3N2) used in animal challenge studies is a mouse-adapted virus derived from a PR8 reassortant virus × -171 (ref. 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…A/Brisbane/10/2007-ma (H3N2) used in animal challenge studies is a mouse-adapted virus derived from a PR8 reassortant virus × -171 (ref. 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…To define the potential mechanism of action of mAbs, we performed a fusion assay using a specifically designed cell line. In previous studies, we studied the mechanism of action in which antibodies act on a particular virus, focused upon how viruses are blocked by antibodies after endocytosis [ 35 , 36 ]. In this study, a membrane fusion inhibition assay confirmed that low-pH-induced conformational change and cell-cell fusion were inhibited by NP-19-9 and 11B6.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has more potential to be utilized for clinical development, because the stem region has fewer mutations than the receptor binding site. Additionally, several groups, including ours, have elucidated unconventional virus neutralizing mechanisms that affect the infection steps that occur after membrane fusion[58,59].…”
Section: Discussionmentioning
confidence: 99%